2005
DOI: 10.1103/physrevlett.95.223903
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Ultraviolet Fourier-Transform Spectroscopy with High Order Harmonics

Abstract: Extreme ultraviolet fourier-transform spectroscopy with high order harmonicsKovacev, M; Fomichev, SV; Priori, E; Mairesse, Y; Merdji, H; Monchicourt, P; Breger, P; Norin, Johan; Persson, Anders; Lhuillier, A; Wahlström, Claes-Göran; Carre, B; Salieres, P General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…This radiation is typically emitted in a train of attosecond pulses with excellent spatial and temporal coherence, as shown in various interferometric and spectroscopic measurements [4][5][6][7][8][9][10][11][12]. As a result, interferometry with high harmonics found important applications in e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This radiation is typically emitted in a train of attosecond pulses with excellent spatial and temporal coherence, as shown in various interferometric and spectroscopic measurements [4][5][6][7][8][9][10][11][12]. As a result, interferometry with high harmonics found important applications in e.g.…”
mentioning
confidence: 99%
“…Two main types of HHG interferometers have been devised. In one scheme, the near-infrared fundamental driving pulse is split into two phase-locked pulses with an adjustable time delay, and this pulse pair is subsequently used for HHG [5,[7][8][9]. Although this method has been successfully used it is typically limited by the stability of the optical interferometer.…”
mentioning
confidence: 99%
“…It has been shown that two sources have relative timing jitter in the zeptosecond range [25]. Since beamsplitters are not readily available in the HHG spectral range, and spatial wavefront division cannot create two closely-separated sources [26], we instead split the driving infrared femtosecond laser pulse and create two separate foci in the same gas source [18,19,27]. The two 800-nm 50-fs laser pulses are delayed in a common-path arrangement with a time-delay step size of 27 attoseconds over a total delay of 27 fs.…”
Section: Methodsmentioning
confidence: 99%
“…A delay jitter of a tenth of a wavelength in FTS can deteriorate the quality of retrieved power spectrum [18]. The accuracy of the delay step limits the highest optical frequency that can be spectrally resolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation